ANALISIS PERKEMBANGAN KARAKTERISTIK ANAK SEKOLAH DASAR DI SDN TELUK PUCUNG I BEKASI - Husna Farhana (Universitas Ahmad Dahlan, 2020)
This research was conducted to analyze the development of the characteristics of elementary school-age children, the aim is to find out the efforts made by the school, especially teachers in developing the characteristics of children in school, besides also to find out what obstacles the schools have especially teachers in applying the program To develop the characteristics of children in primary schools with these objectives, the researchers submitted a study entitled